2017
DOI: 10.1016/j.foodpol.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Is increasing inorganic fertilizer use for maize production in SSA a profitable proposition? Evidence from Nigeria

Abstract: Inorganic fertilizer use across Sub-Saharan Africa is generally considered to be low. Yet, the notion that fertilizer use is too low is predicated on the assumption that it is profitable to use rates higher than currently observed. There is, however, limited empirical evidence to support this. Using a nationally representative panel dataset, this paper empirically estimates the profitability of fertilizer use for maize production in Nigeria. We find that fertilizer use in Nigeria is not as low as conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 39 publications
11
108
0
Order By: Relevance
“…While the relatively high inorganic fertilizer application rates observed in Nigeria are exceptional across the LSMS-ISA countries (Sheahan and Barrett, 2017), the findings by Liverpool-Tasie et al (2017), which, in Nigeria, are also confirmed for rice (Liverpool-Tasie, 2016), underscore the need to better understand the agro-ecological and market conditions under which inorganic fertilizer use in particular, and other agricultural technologies in general, are profitable. Also, in the absence of adequate ex post coping mechanisms, still higher returns will be needed for fertilizer (and other modern) input use to be profitable or optimal (Dercon and Christiaensen, 2011).…”
Section: A Micro-economic Update On African Agriculturementioning
confidence: 98%
See 2 more Smart Citations
“…While the relatively high inorganic fertilizer application rates observed in Nigeria are exceptional across the LSMS-ISA countries (Sheahan and Barrett, 2017), the findings by Liverpool-Tasie et al (2017), which, in Nigeria, are also confirmed for rice (Liverpool-Tasie, 2016), underscore the need to better understand the agro-ecological and market conditions under which inorganic fertilizer use in particular, and other agricultural technologies in general, are profitable. Also, in the absence of adequate ex post coping mechanisms, still higher returns will be needed for fertilizer (and other modern) input use to be profitable or optimal (Dercon and Christiaensen, 2011).…”
Section: A Micro-economic Update On African Agriculturementioning
confidence: 98%
“…Binswanger-Mkhize and Savastano (2017) then assess the current input application rates within the macro-context of Africa’s current population density and market access. This is followed by a case study of the actual profitability of fertilizer use in Nigeria (Liverpool-Tasie et al (2017)), drawing attention to a core micro-economic principle driving input adoption, namely profitability. The fourth paper explores the potential for increasing crop output from closing the gender productivity gap (Palacios-Lopez et al, 2017b).…”
Section: A Micro-economic Update On African Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies emphasized associated problems with the inappropriate application and improper management of inorganic fertilizers, including increased consumption of fossil fuels, leach out of soil, pollution of water basins, destruction of micro-organisms and advantageous insects, increased sensitivity of the crop to diseases, and reduced soil fertility, all of which tend to impose irreparable damage to the overall system. On the other end of the spectrum, organic fertilizers seem to be capable of addressing these problems [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, a major concern in semi-arid regions is the further loss of SOM and, hence, deteriorated fertility. A number of factors contribute to reduced crop residue mulch and, hence, loss of SOM; these include overgrazing, burning the residues, termites, sparse vegetation, limited moisture, and over-ploughing [16,17].…”
Section: Introductionmentioning
confidence: 99%